Acute effect of sorghum flour-containing pasta on plasma total polyphenols, antioxidant capacity and oxidative stress markers in healthy subjects: A randomised controlled trial - Khan, Imran; Yousif, Adel M.; Johnson, Stuart K.; Gamlath, Shirani (Clinical nutrition (Edinburgh, Scotland), 2015)
It has been previously reported that pasta containing wholegrain sorghum flour exhibits high content of polyphenols and antioxidant capacity and hence might enhance antioxidant status and reduce markers of oxidative stress in vivo; however no clinical studies have yet been reported. Therefore, the present study assessed the effect of pasta containing red or white wholegrain sorghum flour on plasma total polyphenols, antioxidant capacity and oxidative stress markers in humans. The study was registered with the Australian New Zealand Clinical Trials Registry (ACTRN: 12612000324819). In a randomised crossover design, healthy subjects (n = 20) consumed three test meals of control pasta (CP), 30% red sorghum pasta (RSP) or 30% white sorghum pasta (WSP), 1–2 wk apart. The test meals were consumed as breakfast after an overnight fast. Blood samples were obtained at fasting and 2 h after consumption and analysed for total polyphenols, antioxidant capacity, superoxide dismutase (SOD) activity, protein carbonyl and 8-isoprostanes. Compared to baseline, the 2 h post-prandial levels following the RSP meal of plasma polyphenols, antioxidant capacity and SOD activity were significantly (P < 0.001) higher while the protein carbonyl level was significantly lower (P = 0.035). Furthermore, net changes in polyphenols, antioxidant capacity and SOD activity were significantly (P < 0.001) higher while protein carbonyl were significantly (P = 0.035) lower following consumption of the RSP meal than the CP meal. The results demonstrated that pasta containing red wholegrain sorghum flour enhanced antioxidant status and improved markers of oxidative stress in healthy subjects.